Penile mass in dog - Morton, Mark; Pohlman, Lisa M. (My University, 2015)
A 2-year-old, castrated retriever crossbreed presented with a history of hemorrhagic discharge from the prepuce.
Keywords: Applied cytology; Oncology; Transmissible venereal tumor